Understanding health professionals' intention to use telehealth in Yemen: using the DeLone and McLean IS success model - Al-Fadhli, Abdulrahman Al-Ezzi; Othman, Marini; Ali, Nor'ashikin; Aljamrh, Bassam Ali Ali (Springer, 2017)
Telehealth is considered as an innovative technology for enhancing healthcare systems in rural areas. Rural areas in Yemen are suffering from poor healthcare due to limited access of health services. Therefore, the aim of this study is to determine Health Professionals’ intention to use Telehealth in Yemen. Delone and Mclean model has been developed by integrating indirect factor “Anxiety” from the unified theory of acceptance and use of technology (UTAUT). A quantitative approach based on self-administrated questionnaire has been deployed. SPSS has been used for analysis purposes. Results found that factors System quality, Information quality, Service quality, Net benefit and User satisfaction had a positive and significant impact on Intention to use Telehealth. The results revealed that the Health Professionals have intention to use the Telehealth to do their duties.